2022
DOI: 10.1097/spc.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Tests to uncover and assess breathlessness: a proposed framework

Abstract: Purpose of ReviewBreathlessness is a common, distressing, and limiting symptom that many people avoid by reducing their activity. This review discusses exertional tests that can be used for uncovering and assessing breathlessness depending on the person's severity of illness, function, the setting, and aim of the assessment. Recent FindingsStandardized exertional tests are useful to uncover 'hidden' breathlessness earlier in people who may have adapted their physical activity to limit their breathing discomfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These findings have several important implications. First, they reinforce the use of CPET as the gold standard method to evaluate exertional breathlessness in terms of underlying mechanisms, treatment effects 8,[33][34][35] , and also the presence and level of abnormal exertional breathlessness. Second, the CPET normative reference equations provide the first valid benchmark for defining abnormal exertional breathlessness.…”
Section: Discussionmentioning
confidence: 64%
“…These findings have several important implications. First, they reinforce the use of CPET as the gold standard method to evaluate exertional breathlessness in terms of underlying mechanisms, treatment effects 8,[33][34][35] , and also the presence and level of abnormal exertional breathlessness. Second, the CPET normative reference equations provide the first valid benchmark for defining abnormal exertional breathlessness.…”
Section: Discussionmentioning
confidence: 64%
“…Develop standardised exertional tests to uncover “hidden” breathlessness in individuals who have reduced physically demanding activities to avoid breathlessness 5 …”
Section: Discussionmentioning
confidence: 99%
“…Breathlessness is highly prevalent in people with serious life-limiting conditions; it is the most common symptom of chronic respiratory diseases, but also prevalent in cardiac and neurological conditions, and some advanced cancers. Ekstro ¨m [2] explores exertional tests for both uncovering and assessing breathlessness and considers these in relation to key factors such as the person's severity of illness, function, the setting and aim of the assessment. To overcome the challenges of recall and reduced physical activity, the review recommends standardized testing to uncover under-reported or ''hidden'' breathlessness in people with reduced activity (which may be reduced in response to the breathing distress at exertion) and to provide valid assessment of breathlessness severity across people and for the individuals over time.…”
mentioning
confidence: 99%
“…Each of these contributions to this issue show how the field has progressed in the last year but each contribution also clearly identifies key areas for future research. Improved measurement of breathlessness in relation to standardized exertional testing is needed including reference equations for normal breathlessness for different levels of exertion, validation of breathlessness tests for people with conditions other than COPD, and the development of tests to evaluate severity and change in breathlessness in people with more severe illness for use at point of care [2]. More research is needed on cough mechanisms and how they differ between different diseases, as well as whether cough treatment affects cough-associated symptoms such as fatigue, anxiety, pain and social isolation [3].…”
mentioning
confidence: 99%